Hybrid Meta-Heuristic Algorithms For Solving Vehicle Routing Problems - Adnan, Sarah Hazwani (2021)
Therefore, a heuristic approach which integrates Fully Informed Particle Swarm (FIPS) with Self-Adaptive Differential Evolution (SaDE) is proposed, namely FIPSaDE. The development of a systematic fleet scheduling system will not only minimize the possible wastage in terms of time and cost; but will also smooth the operations of logistic distribution and helps in managing and achieving long-term resource sustainability